Lateralization of hippocampal nitric oxide mediator system in people with Alzheimer disease, multi-infarct dementia and schizophrenia - Kristofiková, Zdena; Kozmiková, Iryna; Hovorková, Petra; Rícný, Jan; Zach, Petr; Majer, Emmerich; Klaschka, Jan; Rípová, Daniela (Neurochemistry international, 2008)
There is evidence that brain lateralization underlying hemispheric specialization can be observed also at biochemical level. However, hemispheric differences in nitric oxide mediator system have not yet been evaluated. The hippocampus and planum temporale are highly asymmetrical regions but the degree of their laterality is altered in demented or psychotic people. In the study, l-glutamate/l-arginine/l-citrulline concentrations, nitric oxide synthase activities/expressions and nitrites/nitrates levels were estimated in autoptic hippocampi. Right/left laterality in endothelial synthase activity and in nitrites/nitrates was observed in controls. Lateral changes were estimated in patients with Alzheimer disease (a marked increase in activities of constitutive synthases and in expression of inducible enzyme in the left side) and schizophrenia (an increase in activities of all enzymes especially in the right side). Significant shifts from positive to negative correlations were found between laterality of some components of nitric oxide pathway and of planum temporale volumetry under pathological conditions. The hippocampal nitric oxide system appears to be globally right/left lateralized, especially via actions of highly asymmetrical endothelial synthase. The results suggest a specific involvement of all synthases in the development of selected diseases and show that lateral analyses are of sufficient sensitivity to reveal subtle links. The volumetric asymmetry of the planum temporale as a marker of handedness is not probably simply linked to brain laterality at biochemical level but reflects alterations due to pathological processes.
Keywords: multiinfarktová demence; funkční lateralita; Aged; Schizophrenia; Aged, 80 and over; izoenzymy; signální transdukce; Signal Transduction; Glutamine; glutamin; senioři; synthasa oxidu dusnatého; Hippocampus; lidé; Nitrites; Nitrates; Alzheimer Disease; citrulin; Female; Citrulline; Nitric Oxide; senioři nad 80 let; arginin; Isoenzymes; Male; ženské pohlaví; hipokampus; Humans; mužské pohlaví; Alzheimerova nemoc; oxid dusnatý; schizofrenie; Arginine; Dementia, Multi-Infarct; dusičnany; Nitric Oxide Synthase; Functional Laterality; dusitany